2018
DOI: 10.1080/21645515.2018.1543525
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus (EBV) status in colorectal cancer: a mini review

Abstract: Epstein-Barr virus (EBV) is a well-characterized oncovirus, associated with several malignancies. The complex and heterogeneous nature of colorectal cancer (CRC) has led to many epidemiological causal associations with CRC. However, a direct causal link between microbial infections and CRC has not been established yet. Our review indicates that the current evidence for the presence and role in EBV in CRC is insufficient and contradictory. The design of the analyzed studies, sample size as well as methodology u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 78 publications
(90 reference statements)
0
41
0
3
Order By: Relevance
“…The highest reported EBV-positivity in CRC was up to 46%, with the majority of the studies reporting EBV positivity of 20–40% [ 19 , 28 , 41 , 42 ]. Our study indicated the individual presence of EBNA1 and LMP1 genes of EBV in 14% and 25% of the samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest reported EBV-positivity in CRC was up to 46%, with the majority of the studies reporting EBV positivity of 20–40% [ 19 , 28 , 41 , 42 ]. Our study indicated the individual presence of EBNA1 and LMP1 genes of EBV in 14% and 25% of the samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, EBV is a double-stranded DNA gamma-herpes virus, which infects 90% of the adult population [ 2 , 19 ]. EBV causes infectious mononucleosis and various epithelial and lymphoproliferative malignancies such as nasopharyngeal and gastric carcinoma as well as several B-cell lymphomas and T-cell/NK lymphomas [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual role of the strong anti-CMV immune responses in oesophageal and pancreatic cancer TIL seen in Patient 7 requires further biological dissection. Similarly, a link between EBV and CRC was recently reviewed by Bedri and colleagues [44], wherein several lines of evidence based on EBV nucleic acids and proteins, but not T-cell responses in patient samples, were summarised. CMV-directed T cells have been shown to infiltrate primary melanoma lesions in mice and maintain immune reactivity despite PD-1 expression [45].…”
Section: Cmv–host Interactions In Cancermentioning
confidence: 99%
“…Seroprevalence in adulthood is over 98%. Though, a direct connection between EBV infection and CRC has not yet been established [18].…”
Section: Introductionmentioning
confidence: 99%